Sleep in Myopic and Non-Myopic Children - Ostrin, Lisa A. (Transl Vis Sci Technol, 2020)
PURPOSE: To examine differences in sleep between myopic and non-myopic children. METHODS: Objective measurements of sleep, light exposure, and physical activity were collected from 91 children, aged 10 to 15 years, for two 14-day periods approximately 6 months apart. Sleep parameters were analyzed with respect to refractive error, season, day of the week, age, and sex. RESULTS: Myopic children exhibited differences in sleep duration by day of the week (P < 0.001) and season (P = 0.007). Additionally, myopic children exhibited shorter sleep latency than non-myopic children (P = 0.04). For all children, wake time was later (P < 0.001) and sleep duration was longer (P = 0.03) during the cooler season compared with the warmer season. On weekends, children went to bed later (P < 0.001), woke up later (P < 0.001), and had increased sleep duration (P < 0.001) than on weekdays. Younger children exhibited earlier bedtime (P = 0.005) and wake time (P = 0.01) than older children. Time spent outdoors was positively associated with sleep duration (P = 0.03), and daily physical activity was negatively associated with wake time (P < 0.001). CONCLUSIONS: Myopic children tended to have more variable sleep duration and shorter latency than non-myopic children. Sleep patterns were influenced by season, day of the week, age, time outdoors, and activity. TRANSLATIONAL RELEVANCE: Myopic children tended to have more variable sleep duration and shorter latency than non-myopic children, which may reflect previously reported differences in environmental and behavioral factors between refractive error groups.